2021
DOI: 10.1097/nna.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shared Governance on Nurse-Sensitive Indicator and Satisfaction Outcomes by Magnet® Recognition Status

Abstract: OBJECTIVE: Researchers examined associations between Index for Professional Nursing Governance (IPNG) types and outcomes. BACKGROUND: Effects of professional nursing governance on nurse-related outcomes by Magnet ® status are not well studied. METHODS: Associations were evaluated between average IPNG scores from 2170 RNs, and nursesensitive indicators (NSIs) as well as patient and RN satisfaction outcomes (N = 205 study units; 20 hospitals), following Magnet requirements. RESULTS: Magnet hospitals had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Accordingly, increasing nurses' meaningful participation in decision-making can improve their job satisfaction. Consistently, Speroni, Wisner, Ober et al (2021) suggested that expanding professional governance can be the key strategy to enhance nurse-related outcomes, including job satisfaction. Professional governance can be successfully implemented by increasing frontline nurses' control over their professional practice in their affiliating organizations, increasing their ability to engage in committees related to strategic planning and management of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, increasing nurses' meaningful participation in decision-making can improve their job satisfaction. Consistently, Speroni, Wisner, Ober et al (2021) suggested that expanding professional governance can be the key strategy to enhance nurse-related outcomes, including job satisfaction. Professional governance can be successfully implemented by increasing frontline nurses' control over their professional practice in their affiliating organizations, increasing their ability to engage in committees related to strategic planning and management of resources.…”
Section: Discussionmentioning
confidence: 99%
“…This 20-site study examined differences in the 50-item IPNG scores (traditional, shared, and self-governance) for 2170 RNs by unit-based nurse-related outcomes of nurse-sensitive indicators (NSIs), patient satisfaction, and RN satisfaction. They reported IPNG and nurse-related outcome differences by location (United States and non–United States) 14 and by Magnet status 15 . Summary findings demonstrated that study units scoring as shared governance or self-governance had higher percentages of nurse-related outcomes outperforming unit benchmarks than for study units scoring as traditional governance.…”
Section: Instruments To Measure Professional Governancementioning
confidence: 95%
“…The parent study was a cross-sectional survey of nursing staff, and this investigation is a secondary analysis of a subset of the parent study. [14][15] The system's institutional review board deemed this research exempt. All participants provided informed consent in the online survey platform (SurveyMonkey).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations